Efficacy and safety of Hybrid-APC for the ablation of Barrett’s esophagus - Manner, Hendrik; May, Andrea; Kouti, Ioanna; Pech, Oliver; Vieth, Michael; Ell, Christian (Surgical Endoscopy, 2016)
Background and study aim: After thermal ablation of Barrett’s esophagus (BE), stricture formation is reported in 5 to over 10 % of patients. The question arises whether submucosal fluid injection prior to ablation may lower the risk of stricture formation. The aim of the present study was to evaluate the efficacy and safety of the new technique of Hybrid-APC which combines submucosal injection with APC. Patients and methods: Patients who had a residual BE segment of at least 1 cm after endoscopic resection of early Barrett’s neoplasia underwent thermal ablation of BE by Hybrid-APC. Prior to thermal ablation, submucosal injection of sodium chloride 0.9 % was carried out using a flexible water-jet probe (Erbejet 2; Erbe Elektromedizin, Tuebingen, Germany). Check-up upper GI endoscopy was carried out 3 months after macroscopically complete ablation including biopsies from the neo-Z-line and the former BE segment, and recording of stricture formation. Results: From May 2011 to November 2012, a total of 60 patients (pt) were included in the study [55 pt male (92 %); mean age 62 ± 9 years, range 42–79]. Ten patients were excluded from the study. In the remaining 50 pt, Hybrid-APC ablation and check-up endoscopy at 3 months were carried out. Forty-eight out of 50 pt (96 %; ITT: 49/60, 82 %) achieved macroscopically complete remission after a median of 3.5 APC sessions [SD 2.4; range 1–10]. Freedom from BE was histopathologically observed in 39/50 patients (78 %). There was one treatment-related stricture (2 %). Minor adverse events of Hybrid-APC were observed in 11 patients (22 %). Conclusions: According to this pilot series, Hybrid-APC was effective and safe for BE ablation in a tertiary referral center. The rate of stricture formation was only 2 %. Further studies are required to confirm the present results. German Clinical Trials Register: DRKS00003369.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Argon plasma coagulation; Barrett’s esophagus; Hybrid-APC